DETERMINASI DIVERSIFIKASI VERTIKAL PRODUK OLAHAN JAMBU MERAH - Marina Ekawati; Yuli Wibowo; Kiky Chily Arum Dalu; Nurhayati Nurhayati (JURNAL AGROTEKNOLOGI, 2019)
Red guava as tropical fruit is widely cultivated in Indonesia. The abundant production of red guava is not accompanied by the processing of this fruit with 30-40% post harvest damage. This study aimed to determine the vertical diversification of red guava products. The study used a descriptive and analytical approach. Vertical diversification of red guava products were juice, puree, jam, “dodol”, and crakers. The lowest cost of production was guava juice i.e Rp 5,398.-per unit. Evaluation of sensory showed that guava juice was the most preferred for taste and aroma with score 4.30 (like) and 3.73 (like). The most preferred product for color was “dodol” with score 4.30 (like). Based on production cost and preferred value, guava juice was the most potential as a vertical diversification of guava product than the other products (puree, jam, “dodol”, and crakers). Keywords: vertical diversification, jam, juice, production cost, red guava